Unveiling the Significance of Shodhan with Special Emphasis on Samanya Shodhana of Pittala (International Journal of Ayurveda and Pharma Research, 2024)
Shodhana, a crucial procedure in the pharmaceutical preparation of metals and minerals, aims to eliminate impurities and undesirable properties from raw materials, rendering them suitable for further processing. This study focuses on Samanya Shodhana of Pittala, a Mishra Loha, following the guidelines outlined in Rasa Ratna Samucchya. The process involves heating raw Pittala until red-hot and subsequently quenching it in Tila Taila, Takra, Gomutra, Kanji, and Kulatha Kwatha for seven iterations. Post-Shodhana, observations were made regarding the weight loss of Pittala, as well as pH and color changes in the respective liquid media. Results indicate a total weight loss of 7.0% in Pittala after Samanya Shodhana, suggesting effective impurity eradication.